2023
DOI: 10.1111/os.13847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Modified K‐wire Fixation with Open Reduction and Internal Fixation (ORIF) for Unstable Colles Fracture in Elderly Patients

Lin Zhang,
Haoming Jiang,
Jin Zhou
et al.

Abstract: ObjectiveOpen reduction and internal fixation (ORIF) is the standard treatment of unstable Colles fracture among the elderly. Modified percutaneous K‐wire fixation is becoming increasingly popular in recent years. However, there is controversy concerning its appropriate use. This study aimed to compare the early safety and efficacy of the two different treatments and provide an alternative method for the treatment of unstable Colles fracture among the older population.MethodsElectronic medical records of 60 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thorninger et al also found that VLPF does not superiorly improve the functional outcomes after 5 weeks, 6 months, and 12 months compared to casting, and complication rates are similar [44]. However, modified K-wire fixation might be a safe, effective, rapid, and minimally invasive surgical option owing to higher patient satisfaction, shorter operation time, and a lower complication rate compared to ORIF [45].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Thorninger et al also found that VLPF does not superiorly improve the functional outcomes after 5 weeks, 6 months, and 12 months compared to casting, and complication rates are similar [44]. However, modified K-wire fixation might be a safe, effective, rapid, and minimally invasive surgical option owing to higher patient satisfaction, shorter operation time, and a lower complication rate compared to ORIF [45].…”
Section: Surgical Treatmentmentioning
confidence: 99%